Heteroleptic, two-coordinate [M(NHC)N(SiMe3)2] (M = Co, Fe) complexes: synthesis, reactivity and magnetism rationalized by an unexpected metal oxidation state12. Issue 4 (5th January 2017) - Danopoulos, Andreas A.; Braunstein, Pierre; Monakhov, Kirill Yu.; van Leusen, Jan; Kögerler, Paul; Clémancey, Martin; Latour, Jean-Marc; Benayad, Anass; Tromp, Moniek; Rezabal, Elixabete; Frison, Gilles
Abstract : Magnetism, XPS and XANES data of the title complexes imply M II centres coupled to one ligand-delocalized electron. Abstract : The linear, two-coordinate and isostructural heteroleptic [M(IPr)N(SiMe3 )2 ] (IPr = 1, 3-bis(diisopropylphenyl)-imidazol-2-ylidene), formally M I complexes (M = Co, 3 ; Fe, 4 ) were obtained by the reduction of [M(IPr)ClN(SiMe3 )2 ] with KC8, or [Co(IPr)N(SiMe3 )2 2 ] with mes*PH2, mes* = 2, 4, 6- t Bu3 C6 H2 . The magnetism of3 and4 implies Co II and Fe II centres coupled to one ligand-delocalized electron, in line with XPS and XANES data; the ac susceptibility of4 detected a pronounced frequency dependence due to slow magnetization relaxation. Reduction of [Fe(IPr)ClN(SiMe3 )2 ] with excess KC8 in toluene gave the heteronuclear 'inverse-sandwich' Fe–K complex7, featuring η 6 -toluene sandwiched between one Fe 0 and one K + centre.